Canvas+: Proposed New Business Model Canvas to Achieve Profitability and Sustainability Goals in PT Berlin Pharma Indonesia - Naulita, Puty; Anggoro, Yudo (Jurnal Perilaku dan Strategi Bisnis, 2023)
The purpose of this research is to find out how sustainability goals can support profitability in PT Berlin Pharma Indonesia. The company is committed to achieving sustainability goals while facing the profitability issue in the VUCA world. This study used a simple mixed approach, using a survey of 30 respondents from all departments in the company as a quantitative method and interviews with 5 top management and senior management as a qualitative method. The questions are based on Better Business Scan Framework to understand the gap between the intention and realization of the company as a basis to define the new business strategy. The result proposes that Canvas+ is a new strategy to upgrade the existing business model of the company.  The nexus approach can be used to align the work among departments to synergize sustainability effects.